2021
DOI: 10.1021/acs.orglett.1c00201
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Catalyzed Asymmetric Allylic Alkylation of Achiral MBH Carbonates with 3,3′-Bisindolines: Enantioselective Construction of Quaternary Stereogenic Centers

Abstract: The asymmetric allylic alkylation (AAA) of achiral Morita−Baylis−Hillman (MBH) carbonates with 3,3′-bisindolines under the catalysis of amino-acid-derived bifunctional phosphines was accomplished. With the AAA approach introduced herein, challenging 3,3′-bisindolines bearing an all-carbon quaternary stereocenter (C3a) have been constructed in good yields with good to excellent enantioselectivties. In addition, the synthetic value of this protocol was demonstrated by the facile synthesis of the core skeleton of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Experimental outcomes and density functional theory calculations demonstrated that the oxamide coordination to palladium to form a favorable chiral environment is crucial for the corresponding regio- and enantioselective control. Inspired by the unique catalytic behavior of COAP in pallidum-catalyzed asymmetric allylic alkylation reactions, we proposed that COAP-palladium could catalyze asymmetric allylic alkylation of azlactones with MBH carbonates, which might provide an alternative approach for the construction of unnatural chiral α-amino acid derivatives. In this transformation, the catalyst must simultaneously control both linear regioselectivity and a chiral quaternary carbon center.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental outcomes and density functional theory calculations demonstrated that the oxamide coordination to palladium to form a favorable chiral environment is crucial for the corresponding regio- and enantioselective control. Inspired by the unique catalytic behavior of COAP in pallidum-catalyzed asymmetric allylic alkylation reactions, we proposed that COAP-palladium could catalyze asymmetric allylic alkylation of azlactones with MBH carbonates, which might provide an alternative approach for the construction of unnatural chiral α-amino acid derivatives. In this transformation, the catalyst must simultaneously control both linear regioselectivity and a chiral quaternary carbon center.…”
Section: Introductionmentioning
confidence: 99%
“…While the Morita–Baylis–Hillman (MBH) reaction has been proved to be a useful process for C–C bond formation, 11 the acetates or carbonates of the MBH products have also been showed to be a powerful class of allylic alkylation reagents that can allylate a variety of nucleophiles with the aid of suitable nucleophilic catalysts. 12 More specifically, an appropriate nucleophilic catalyst may convert an MBH adduct into an active catalytic intermediate via an S N 2′ process, which can then be attacked by suitable nucleophiles either to afford compound D by an S N 2 substitution or to deliver compound E through an S N 2′ displacement 12 c ,13 (Scheme 1c). To the best of our knowledge, examples concerning the catalytic asymmetric versions of the S N 2′–S N 2 type process reported in the literature are rare.…”
Section: Introductionmentioning
confidence: 99%